Memórias literárias: a relevância da formação literária do professor para a mediação da literatura na educação básica - Carrijo, Ranyelle Rosa (2022)
This research was born from a personal concern, when we realized, from our experience as teachers and pedagogical coordinator of the Municipal Network of Aparecida de Goiânia, that many pedagogues and Portuguese Language teachers do not have as one of their main focuses of interest the formation of literary readers in Basic Education. Our hypothesis, based on observation, is that the lack of initial and continuing education, which includes the reading of literary texts and their mediation, as well as adequate public policies, are obstacles to the performance of these professionals in the teaching of literature. At this point, we should ask: how can continuing education contribute to the mediation of literary texts in Basic Education? The main point of the discussion is to investigate the literary training of teachers in Brazil and how it can be a determining factor in the teaching of literature so that, based on this diagnosis, we can contribute to a reflection about the teaching of literature. We believe that, in order to teach literature in school, it is essential that the teacher be an experienced reader himself and act as a mediator, leading the student to construct the latent meanings in the literary text. As a theoretical basis, the study resorted to Antonio Candido (1972, 1989, 1995), Regina Zilberman (1985, 2001, 2012), TzvetanTodorov (2009), Teresa Colomer (2003, 2007), Julio Cortázar (2006), Paulo Freire (1921, 1987), among others. As literary corpus, some children's short storiesby Clarice Lispector wereselected: A Vida Íntima de Laura (2012), O Mistério do Coelho Pensante (2013), A mulher Que Matou os Peixes (2017), Quase de Verdade(2014), Doze lendas brasileiras: Como nasceram as estrelas (2014). The research took place in a municipal school in Aparecida de Goiânia, with the teachers of Elementary I. As a starting point, a reading circle/conversation was held with three classes between eight and eleven years old, in order to diagnose possible barriers between readers and literary reading. Subsequently, we interviewed the teachers. The diagnoses subsidized the literature teaching workshops for teachers, based on theoretical and literary texts, aiming, on one hand, to provide moments of discussion about literature teaching and, on the other, to delight in Clarice Lispector's short stories. Both the interviews and the workshops were developed in a virtual environment, as a measure to prevent the dissemination of Covid-19 (an infectious disease caused by the new coronavirus - SARS-CoV-2). The research also includes an educational product in audiovisual media entitled "Literary Memories", which is linked to the StrictoSensu Professional Master's Degree of the Graduate Program in Teaching in Basic Education of the Center for Teaching and Applied Research in Education (CEPAE) of the Federal University of Goiás (UFG) and, therefore, is still available on the website of the Graduate Program in Teaching in Basic Education (https://pos.cepae.ufg.br).